The Influence Of Mathematics Learning Media On Students' Creative Mindsets Based On Philosophy Of Science - Ririn Sasanti; Siti Masitoh; Mochamad Nursalim (Institute of Computer Science (IOCS), 2022)
Improvement in the quality of education, one of which is indicated by improving learning outcomes, cannot be separated from efforts to improve learning innovations in learning media are very much currently, especially in the field of mathematics with the existence of learning media eating the creative and innovative mindset of students is developing well. The use of teaching aids in the learning process in students is very helpful in increasing the understanding of concepts and skills in the subject matter taught, especially mathematics lessons, in philosophy of science and education there are several aspects that are the basis of learning media, namely aspects of ideas and facts, as well as abstract and concrete both theoretically and practically. The approach of philosophy of science and education ontologically, epistemologically, and axiologically in the development of learning media if summarized in accordance with their practical objectives, will be able to form practical values that lead to the ability of student learning outcomes.